Research of key characteristics of project-based firms and their organizational culture - N. V. Titova; S. A. Titov (Вестник университета)
The purpose of the study is to identify specifics of the organizational culture ofproject-based companies. Based on generalizations of the results of existing research, the definition of a project-based company has been clarified. The main characteristics that distinguish project-based firms from process-based firms have been identified. Based on this characteristics, it has been concluded that such companies differ not only in their organizational structure, content of activities and composition of participants, but also in their organizational culture. Among these features of organizational culture, the authors have included: focus on the final result, team interaction, informal communications, internal motivation of employees, active interaction with the customer. The conclusion has been made about the specifics of the project culture.